Predicting the outcome in elderly patients of hospital admission for acute care in Paris, France: construction and initial validation of a simplex index. Issue 2 (April 1997) - Zureik, M; Lombrail, P; Davido, A; Trouillet, J L; Tran, B; Levy, A; Lang, T
Abstract : OBJECTIVE: To develop a simple index able to identify at an early stage those elderly patients at high risk of requiring discharge to a residential or nursing home after admission to hospital for acute care. For these patients, early discharge planning might lead to a more effective management and reduce the length of hospitalisation. DESIGN, SETTING, AND PATIENTS: This was a prospective study conducted in two teaching hospitals in Paris, France. A total of 510 consecutive patients was included. They were aged 75 years or more and had been admitted to acute medical care units through the emergency department. MEASUREMENTS: Demographic data, social support, physical disability, mental disability, and pathologic status were assessed shortly after admission (within 24-48 hours). MAIN OUTCOME MEASURES: Outcome of hospitalisation was defined as discharge to home or residential/nursing home. RESULTS: The index, developed by multiple logistic regression, included six variables: the wish of patients' principal career about their returning home after acute hospitalisation, presence of a chronic condition, ability to perform toileting, ability to know the name of the hospital or the city, their age, and their living arrangements. The sensitivity of the index in identifying patients at high risk of requiring discharge to a residential/nursing home was 74.4%, the specificity 63.8% the positive predictive value was 57.8%, and the negative predictive value was 80.6%. CONCLUSIONS: The simple index, using data available very early in the course of hospitalisation, provides an accurate prediction of the hospitalisation outcome. The performance of the index should be tested in other populations and the practical benefits of risk screening should be assessed in a controlled trial to evaluate whether the intervention is useful and without any adverse effects.